The Existence of PSAK 109 An Approach to Realizing Good Zakat Governance in Baznas West Nusa Tenggara - Ocktavia, Annisa Kartika; Mukhlisin, Murniati (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research highlights the importance of standardized accounting and financial reporting in achieving transparency and accountability, which ultimately contributes to higher public trust in BAZNAS. The purpose of this study is to examine the implementation of PSAK No. 109 by BAZNAS in the Province of West Nusa Tenggara, to achieve good zakat governance. The focus of this research is to assess the transparency and accountability of zakat management, as well as the role of good accounting and financial reporting in building public trust in BAZNAS. This study uses primary and secondary data to investigate the implementation of PSAK 109 at BAZNAS in the Province of West Nusa Tenggara. Primary data consists of interviews, while secondary data includes financial reports of BAZNAS in the Province of NTB and related literature studies. The results show that BAZNAS in the Province of NTB has implemented PSAK 109 in terms of recognition, measurement, presentation, and disclosure of zakat transactions. Alignment of zakat institution financial reporting with PSAK 109 can contribute to zakat institutions in realizing good zakat governance, which ultimately leads to optimal zakat realization. To date, attention to zakat governance research has increased, but there has been no specific research on efforts to achieve good zakat governance by BAZNAS in the Province of NTB using PSAK 109.